Analisis Kinerja Keuangan Pada Koperasi CU ( Credit Union ) Daya Lestari Periode 2016-2018 Berdasarkan Rasio Arus Kas - Chrisman Thalib, Chrisman Chrisman (EKONOMIA, 2019)
ABSTRACTÂ The purpose of this study is to find out and analyze the financial performance of the Sustainable Power Credit Union Cooperative for the period 2016-2018 with the application of operating cash flow ratios.The data analysis technique used is financial ratio analysis, which is the operating cash flow ratio in terms of the ratio of operating cash flows, interest, capital expenditure, total debt, and net income.The results of the study show the financial performance of the Daya Lestari Credit Union Cooperative in 2016, 2017, 2018, the operating cash flow ratio, current liabilities show a number of 0.0737, 0.0251, 0.0575 below 1 and financial performance is not good. Cash coverage against Interest 1.8936, 1.3219, 1.8355 financial performance above 1 is good. Capital Expenditures, 0.6337, 0.1124, 0.2429 Financial performance below 1 is not good. Total Debt, 0.0697, 0.0237, 0.0541 Financial performance below 1 is not good. Net Profit, 41,9027, 48,6474, 15,4912 financial performance above 1 Good. It can be concluded that the financial performance of the Cooperative Credit Union measured by the number of operating cash flow ratios during 2016-2018 is said to be poor.Â Â